Factors associated with dengue fever patients attending primary health clinics in Kota Kinabalu (Bangladesh Journal of Medical Science, 2021)
Background: Dengue fever infection has become a major public health concern in Malaysia with frequent epidemics occurring in urban areas. In Sabah, Dengue fever is among the 5 most reported communicable diseases and the district of Kota Kinabalu is among the top 3 districts with the highest number of dengue cases with 563 cases recorded in 2016.Aims and Methodolgy: This study aimed to determine the factors contributing or associated with dengue fever occurrence in Kota Kinabalu. A cross- sectional study was conducted among the primary health care clinic attendees in Kota Kinabalu. Data was collected via a set of structured questionnaires focusing on socio-demographic characteristic of participants, environmental characteristic of households, history of previous exposure to dengue fever, knowledge towards dengue fever and its vector, awareness on dengue fever and mosquito control and dengue fever prevention practices.Results and Recommendations: Among the 350 individual’s that participated in the interview, 53 were dengue fever cases. Subsequently, the prevalence of Dengue fever cases among the study population was calculated with prevalence in percentage concluded as 15.1%. Further analysis revealed that factors such as aged group by years, number of household occupants, staying at dengue outbreak areas, self – reported history of recent mosquito bites, indoor and outdoor storage of open water containers, installed house window screens, knowledge on dengue fever and its vector, practices of wearing protective clothing outdoor and usage of mosquito repellent ointment or creams showed significant association with dengue fever outcomes. However, further studies would need to be conducted to determine if these factors possess a higher threat or risk for dengue fever.Bangladesh Journal of Medical Science Vol.20(4) 2021 p.878-886